THE POSITION OF WOMEN IN THE MAYBRAT TRIBE CUSTOM INHERITANCE - Sri Iin Hartini (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
Customary inheritance law is a law that contains lines of provisions regarding the system and principles of inheritance law, inheritance, heirs, heirs, as well as how the inheritance is transferred to its control and ownership from the heir to the heir. As for what is meant by inherited assets are the assets of heirs who have died, whether the assets have been divided or are still in a state that is not divided. This includes inherited assets, namely heirlooms, marital assets, original assets, inherited assets, and joint assets. Heirs are people who pass on their inheritance to the heirs (heirs). Heir is a term that refers to people who receive inheritance from the heir.The results showed that in the process of inheritance in the Maybrat Tribe community, only sons were entitled to inheritance in the form of customary assets in the form of WAN (Heirloom cloth), beads, land/customary rights, houses/buildings, livestock. Girls have unequal or unequal inheritance rights with boys. Daughters do not get inheritance because if the girl marries, she will leave her family and enter her new family to follow her husband. The Maybrat indigenous people adhere to a patrilineal family system in which family membership is drawn or calculated based on male lineage (father). The patrilineal family system adopted by the Maybrat tribe is a mayoral inheritance system which causes only male descendants to inherit, because the position of a man is more important than his sister who is considered able to take care of and carry on family responsibilities.